Lie down with lions - Follett, Ken (New York : Morrow, 1986)
The intrigue surrounding Russian efforts to assassinate Masud, the leader of the Afghan guerrilla forces battling the Russians, sweeps a young Englishwoman, a French physician, and a roving American into its maelstrom.
Keywords: Afghanistan -- Fiction